How Reliable are Citizen‐Derived Scientific Data? Assessing the Quality of Contrail Observations Made by the General Public. Issue 4 (22nd May 2013) - Fowler, Amy; Whyatt, J. Duncan; Davies, Gemma; Ellis, Rebecca
Abstract: Citizen science projects encourage the general public to participate in scientific research. Participants can contribute large volumes of data over broad spatial and temporal frames; however, the challenge is to generate data of sufficient quality to be useable in scientific research. Most observations made by citizen‐scientists can be independently verified by "experts". However, verification is more problematic when the phenomena being recorded are short‐lived. This article uses a GIS methodology to verify the quality of contrail observations made by the general public as part of the OPAL Climate Survey. We verify observations using datasets derived from a variety of different sources (experts, models and amateur enthusiasts) with different spatial and temporal properties which reflect the complex 3D nature of the atmosphere. Our results suggest that ∼70% of citizen observations are plausible, based on favorable atmospheric conditions and the presence or absence of aircraft; a finding which is in keeping with other, more conventional citizen science projects. However, questions remain as to why the quality of the citizen‐based observations was so high. Given the lack of supporting data on observers, it is impossible to determine whether the dataset was generated by the activities of many participants or a small but dedicated number of individual observers.